Ammonium-assimilating microbiome: A halophilic biosystem rationally optimized by carbon to nitrogen ratios with stable nitrogen conversion and microbial structure. (April 2022) - Zhang, Mengru; Han, Fei; Liu, Zhe; Han, Yufei; Li, Yuke; Zhou, Weizhi
Graphical abstract: Highlights: C/N ratios do not change nitrogen conversions in ammonium-assimilating biosystems. COD, nitrogen and phosphorus are removed simultaneously at different C/N ratios. C/N ratios do not significantly change structure of heterotrophic communities. Abstract: The contradiction between theoretical metabolism of ammonium assimilation and experiential understanding of conventional biosystems makes the rational optimization of the ammonium-assimilating microbiome through carbon to nitrogen (C/N) ratios perplexing. The effect of different C/N ratios on ammonium-assimilating biosystems was investigated in saline wastewater treatment. C/N ratios significantly hindered the nutrient removal efficiency, but ammonium-assimilating biosystems maintained functional stability in nitrogen conversions and microbial communities. With sufficient biomass, higher than 86% ammonium and 73% phosphorus were removed when C/N ratios were higher than 25. Ammonium assimilation dominated the nitrogen metabolism in all biosystems even under relatively low C/N ratios, evidenced by the extremely low abundances of nitrification functional genes. Different C/N ratios did not significantly change the bacterial community structure of ammonium-assimilating biosystems. It is anticipated that the ammonium-assimilating biosystem with advantages of clear metabolic pathway and easy optimization can be applied to nutrient removal and recovery in saline environments.